Dinamika Pembentukan Peraturan Daerah Nomor 1 Tahun 2022 tentang Pendidikan Pancasila dan Wawasan Kebangsaan di Daerah Istimewa Yogyakarta - Eza, Muhammad Chariel Nur (Fakultas Ilmu Pendidikan, 2026)
This research aims to describe the dynamics and challenges in the formation of Regional Regulation No. 1 Year 2022 on Pancasila Education and Nationalism Insight in Yogyakarta Special Region. The focus of the study is directed at the stages of policy formation and its implementation as feedback. The theoretical approach used is David Easton's political system combined with Law Number 12/2011 on the Formation of Legislation. This research uses a qualitative approach with a case study method. Informants were selected purposively. Data sources were obtained through document studies and data collection through interviews, and observation. The results showed that: (1) The dynamics of the formation of Regional Regulation No. 1 of 2022 on Pancasila Education and Nationalistic Insight in the Special Region of Yogyakarta took place through the following aspects: (a) the input aspect is carried out by prioritizing community participation and aspirations, (b) the process aspect runs by involving several parties, institutions and the community (c) the policy has been ratified and becomes an output of the results of a system (d) becomes a feedback that shows evaluation and more intensive public involvement. (2) as well as challenges that hinder the process of forming this regional regulation, namely the low level of public participation so that attention is needed to increase public participation in the formation of a regional policy.